2010
DOI: 10.1007/s00268-010-0484-6
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T Cells in Peripheral Blood, Lymph Node, and Thyroid Tissue in Patients with Medullary Thyroid Carcinoma

Abstract: An increase of FoxP3+ lymphocytes could be shown in peripheral blood of patients with MTC but not in patients with benign goiter; this increase also correlates with findings in lymph nodes and thyroid gland. The number of FoxP3+ cells correlated with the patients' prognosis. Therefore, FoxP3+ lymphocytes are a good diagnostic criterion for malignancy in patients with medullary thyroid carcinoma, and their presence at staging may influence therapeutic decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 19 publications
(16 reference statements)
3
6
1
Order By: Relevance
“…Because Tregs suppress immune response toward tumors, their increased percentage in advanced stages leads to proliferation of the disease, a fact demonstrated by several investigators. The percentage of Tregs in TNG tissue was significantly lower compared with PTC tissue, and these results are comparable to the results shown by Mü ller et al (35) between goiter and medullary thyroid carcinoma. The above data suggest that the malignant microenvironment of thyroid carcinoma, contrary to the benign, either activates the already existing Tregs or enhances their thyroid infiltration.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Because Tregs suppress immune response toward tumors, their increased percentage in advanced stages leads to proliferation of the disease, a fact demonstrated by several investigators. The percentage of Tregs in TNG tissue was significantly lower compared with PTC tissue, and these results are comparable to the results shown by Mü ller et al (35) between goiter and medullary thyroid carcinoma. The above data suggest that the malignant microenvironment of thyroid carcinoma, contrary to the benign, either activates the already existing Tregs or enhances their thyroid infiltration.…”
Section: Discussionsupporting
confidence: 94%
“…This is in contrast to related studies investigating the expression of Tregs in blood samples in ovarian cancer (11), non-small cell lung cancer (13), and even in medullary thyroid cancer (35) in which the percentage of Tregs was significantly higher in the patients compared with healthy blood donors. None of the NK cells populations in peripheral blood presented any differences among the groups.…”
Section: Discussioncontrasting
confidence: 85%
“…Similar to most other types of human cancers, Foxp+ Tregs in either peripheral blood or tumor tissues of human thyroid cancer are increased, compared with blood and tissue samples from normal subjects or those with thyroid nodular goiter (Cunha et al, 2012;French et al, 2010;Gogali et al, 2012;Muller et al, 2010;Szylberg et al, 2014;Yu et al, 2013), which is confirmed in thyroid cancer tissues and matched non-cancer tissues used in this study (Appendix: Supplementary Fig. S1).…”
Section: Discussionsupporting
confidence: 67%
“…In the past few years, increasing evidence has supported that the expression of Foxp3 occurs not only in lymphocyte lineage, but also in non-hematopoietic cells including solid cancer cells (Martin et al, 2010;Triulzi et al, 2013). There are several studies showing that the expression of Foxp3+ Tregs is increased in the peripheral blood and/or cancer tissues of PTC, FTC and medullary thyroid carcinoma (MTC) and that the increased levels of Foxp+ Tregs are associated with a more aggressive form of the cancer and/ or poor clinical prognosis (French et al, 2010;Gogali et al, 2012;Muller et al, 2010;Yu et al, 2013). Very limited information is available for the expression of Foxp3 in thyroid cancer cells, as there are only three reports indicating that thyroid cancer cells of PTC and FTC express Foxp3 which is associated with tumor aggressiveness and resistance to radioiodine treatment (Cunha et al, 2012;Szylberg et al, 2014;Ugolini et al, 2014).…”
Section: Introductionmentioning
confidence: 97%
“…In another report, a significant increase in Treg FoxP3 + lymphocytes in the peripheral blood, in lymph nodes and in thyroid tissues of MTC patients has been observed. Moreover, similar to what was observed in other cancer types, an increase of Tregs in the blood is correlated with the severity of the disease (Muller et al 2010). These data, taken together, indicate that a proinflammatory activity is present in MTC, possibly sustained, among the others, by Th17 cells.…”
Section: Ret and Cancer Immunotherapy In Men2supporting
confidence: 68%